Wikipedia and indigenous language preservation: analysis of Setswana and Punjabi languages - Minhas, Shahid; Salawu, Abiodun (Frontiers in Communication, 2025)
The survival of a language is important for several reasons, some of which are to maintain cultural identity, tradition and wisdom. Therefore, people always try to protect their cultural identity, tradition, and wisdom, thus preserving and promoting their languages. Similarly, indigenous languages, Setswana and Punjabi face challenges in preservation and promotion in this digital world, but their survival is important for preserving cultural identity and heritage. This study examines Wikipedia’s role in promoting and preserving Setswana and Punjabi. The research is framed by the Ethnolinguistic Vitality Theory (EVT), which suggests that language survival lies in reclamation, revitalization, and reinvigoration. A quanti-qualitative approach is used to investigate the issue, integrating quantitative metrics from Wikipedia’s statistical pages with qualitative content analysis of the articles. Data were collected from May 2022 to May 2024, focusing on article counts, edits, active editors, new pages, top edited pages, and views. The study reveals significant disparities in content quality and community engagement between the Setswana and Punjabi Wikipedia editions. It highlights the challenges and opportunities of Wikipedia for enhancing the visibility and usage of indigenous languages. The findings show that Punjabi Wikipedia has a much larger content volume and user base, but comparatively lower recent activity and collaborative depth compared to Setswana Wikipedia. (Setswana) Tswana Wikipedia, while smaller in content volume, demonstrates a more engaged and active editing community, reflected by a higher depth score and a larger number of active users. This indicates a different stage of development and community involvement between the two language editions. Also, the study provides practical recommendations for Wikipedia contributors, language activists, and policymakers, suggesting that increased participation and strategic initiatives can significantly bolster the preservation efforts for these languages.